1999
DOI: 10.1073/pnas.96.19.10661
|View full text |Cite
|
Sign up to set email alerts
|

The Caulobacter crescentus smc gene is required for cell cycle progression and chromosome segregation

Abstract: The highly conserved SMC (Structural Maintenance of Chromosomes) proteins function in chromosome condensation, segregation, and other aspects of chromosome dynamics in both eukaryotes and prokaryotes. A null mutation in the Caulobacter crescentus smc gene is conditionally lethal and causes a cell cycle arrest at the predivisional cell stage. Chromosome segregation in wild-type and smc null mutant cells was examined by monitoring the intracellular localization of the replication origin and terminus by using f l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
223
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 204 publications
(244 citation statements)
references
References 39 publications
19
223
1
1
Order By: Relevance
“…Both SMC and MukB were shown to cooperate with two accessory proteins, which regulate their function [Hirano and Hirano, 2004] and are essential for their activity in vivo [Yamanaka et al, 1996;Mascarenhas et al, 2002]. Inactivation of either of these complexes leads to temperaturesensitive growth due to a severe disturbance of nucleoid organization and chromosome segregation at elevated temperatures [Niki et al, 1991;Britton et al, 1998;Moriya et al, 1998;Jensen and Shapiro, 1999]. This phenotype was shown to be suppressed by mutations that cause excessive negative supercoiling, which suggests a role for these proteins in DNA compaction or folding [Sawitzke and Austin, 2000;Lindow et al, 2002a].…”
Section: Mechansims Of Nucleoid Organizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Both SMC and MukB were shown to cooperate with two accessory proteins, which regulate their function [Hirano and Hirano, 2004] and are essential for their activity in vivo [Yamanaka et al, 1996;Mascarenhas et al, 2002]. Inactivation of either of these complexes leads to temperaturesensitive growth due to a severe disturbance of nucleoid organization and chromosome segregation at elevated temperatures [Niki et al, 1991;Britton et al, 1998;Moriya et al, 1998;Jensen and Shapiro, 1999]. This phenotype was shown to be suppressed by mutations that cause excessive negative supercoiling, which suggests a role for these proteins in DNA compaction or folding [Sawitzke and Austin, 2000;Lindow et al, 2002a].…”
Section: Mechansims Of Nucleoid Organizationmentioning
confidence: 99%
“…These problems are circumvented by a novel technique, which uses the lac or tet repressor fused to a fluorescent protein to specifically decorate tandem repeats of the cognate repressor binding site inserted at a chromosomal locus of interest Straight et al, 1996;Michaelis et al, 1997;Lau et al, 2003]. Using these two approaches, it was shown that bacteria possess mechanisms to orient the replication origin and terminus towards opposite poles in newborn cells Webb et al, 1997;Niki and Hiraga, 1998;Jensen and Shapiro, 1999;Fogel and Waldor, 2005]. This finding already indicates some degree of order within the nucleoid.…”
Section: Spatial Arrangement Of the Bacterial Chromosomementioning
confidence: 99%
See 1 more Smart Citation
“…Initiation of DNA replication results in the rapid formation of a second ParB focus at the opposite pole of the cell. This dynamic localization pattern coincides with the movement of the newly duplicated origin during the cell cycle (Jensen & Shapiro 1999). ParA localizes to the cell poles in C. crescentus but has not been assayed for polar oscillation in living cells (Mohl & Gober 1997).…”
Section: Bacterial Dna Segregation T a Leonard And Others 527mentioning
confidence: 99%
“…In addition to its structural similarity to canonical SMC proteins, MukB shares a common function with prokaryotic SMCs. Both E. coli mukB − strains and smc − strains from Bacillus subtilis and Caulobacter crescentus show temperature-sensitive colony formation and an increase in the number of anucleate cells at the permissive temperature, suggesting a deficiency in chromosome segregation (5,7,(15)(16)(17)(18)(19). Moreover, a convincing array of experiments has demonstrated that MukB functions as a condensin in vitro and in vivo (20)(21)(22)(23)(24)(25)(26)(27)(28).…”
mentioning
confidence: 99%